2020
DOI: 10.32744/pse.2020.4.23
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between emotional and personal well-being and social perception among university teachers and students

Abstract: Взаимосвязь эмоционально-личностного благополучия и социальной перцепции у преподавателей и студентов вузов Введение. Проблема исследования: выявление взаимосвязей социальной перцепции с уровнем внутреннего благополучия участников образовательного процесса. Цели: изучение представлений преподавателей вузов и студентов о других людях, выявление взаимосвязей особенностей этих представлений с показателями эмоционально-личностного благополучия респондентов. Материалы и методы. Исследование социальной перцепции про… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…revealed that the psychodiagnosis carried out by teachers is characterized as haphazardly and not based on psychological and pedagogical technologies. Karapetyan & Glotova (2020) applied the results of the study on the psychological well-being of school teachers with the method of content analysis. Researcher linked the success of his teachers with their psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…revealed that the psychodiagnosis carried out by teachers is characterized as haphazardly and not based on psychological and pedagogical technologies. Karapetyan & Glotova (2020) applied the results of the study on the psychological well-being of school teachers with the method of content analysis. Researcher linked the success of his teachers with their psychological well-being.…”
Section: Introductionmentioning
confidence: 99%